Erratum to: Processing Time Reduction: an Application in Living Human High-Resolution Diffusion Magnetic Resonance Imaging Data (Journal of Medical Systems, (2016), 40, 11, (243), 10.1007/s10916-016-0594-2) - Lori, Nicolás F. (2017)
O artigo encontra-se disponível em: http://hdl.handle.net/1822/52841